Comparison of vagus nerve cross-sectional area between brain-first and body-first Parkinson’s disease - Shuangshuang Dong; Bo Shen; Xu Jiang; Jun Zhu; Haiying Zhang; Yang Zhao; Yaning Chen; Dongfeng Li; Yuanyuan Feng; Yi Chen; Yang Pan; Feng Han; et al. (npj Parkinson's Disease)
Abstract The vagus nerve (VN) is the main neural pathway linking the gut and brain in Parkinson’s disease (PD). In this study, we utilized high-resolution ultrasound to measure the VN cross-sectional area (CSA) in 96 healthy controls (HCs) and 75 PD patients. The PD group was further categorized into three subgroups: PD-preRBD, PD-postRBD, and PD-nonRBD. PD-preRBD was the body-first subtype, and PD-postRBD and PD-nonRBD were the brain-first subtype. The PD group had a significantly lower VN CSA than HCs. Subgroup analysis revealed that the PD-preRBD group tended to exhibit a smaller VN CSA than both the PD-postRBD and PD-nonRBD groups. The VN CSA, specifically the right VN, was significantly correlated with the body-first subtype and some components of PD-related assessment scales. Overall, these findings provide evidence of VN atrophy in PD, especially in body-first PD, suggesting that VN ultrasound could serve as an adjunctive diagnostic tool.